Research progress of support theory and technology of the roadway surrounding rock based on the plastic zone control - Weijun WANG; Lei FAN; Zhiqiang ZHAO; Sen HAN (Meitan xuebao, 2024)
With the increasing depth of coal mining, the stability control of surrounding rock in deep roadway has become one of major problems in the mining field, and the effect of surrounding rock control in deep roadway is directly related to the safe production and health of personnel in underground coal mines. The emergence of plastic zone after roadway excavation is the main reason for the stability of the surrounding rock of the roadway. From the perspective of the formation and expansion of the plastic zone, this paper discusses the intrinsic relationship between the roadway damage mode and the distribution of the plastic zone of surrounding rock on the basis of the results from collating and summarizing the existing roadway damage theory and the theory of the plastic zone of surrounding rock. It is believed that the control of the surrounding rock of roadway is essentially the process of controlling the formation and expansion of the plastic zone of surrounding rock. The expansion of the plastic zone of surrounding rock and the control effect of anchor support on the plastic zone of surrounding rock have become an important theoretical basis for the scientific and effective control of surrounding rock in roadway, and based on this, the authors propose the theory and technology for the stability control of surrounding rock in roadway. The results show that the plastic zone is the product of roadway excavation, and the formation and expansion of the plastic zone of surrounding rock is the result of mine pressure. For deep roadways, the appearance of the plastic zone of surrounding rock is inevitable. Scientific control of plastic zone requires a comprehensive understanding of the role played by the plastic zone in roadway surrounding rock. It is necessary to allow the surrounding rock to release the energy in the rock body through plastic failure, but also to prevent the disorderly expansion of the plastic zone. Therefore, in the process of controlling the surrounding rock of roadway, the self-bearing capacity of the surrounding rock should be given a full play as the main focus, and the support intervention should be supplemented. The control of plastic zone of surrounding rock in deep roadway is global and procedural. The control of the plastic zone of the surrounding rock in the whole life of roadway is divided into three stages. By regulating the shape of the plastic zone and inhibiting the expansion of the plastic zone, the stability control of the surrounding rock of deep roadway is realized.